Career Pocketbook: A Media to Improve Primary School Students’ Career Understanding - Rahim, Maryam; Hulukati, Wenny; Alwi, Nurul Maulida (Jurnal Kajian Bimbingan dan Konseling, 2023)
This study develops a career pocketbook as a career information media to accelerate career understanding among primary school students. This research and development study was completed in a number of stages, including (1) preliminary study, (2) product design, (3) product development following the design, (4) limited tryout, and (5) product revision. For the limited tryout, we conducted a number of tryouts. In the first limited tryout, we involved the experts (from the guidance and counseling field, career guidance and counseling field, and Indonesian language), followed by an individual tryout involving nine students and three counselors, then a small group tryout with 15 students. The primary data were collected using a questionnaire. Further, the data from the experts were analyzed using content analysis, and the experimental data were analyzed using the Wilcoxon test. The results of the analysis of the tryout data suggested that the developed career pocketbook is feasible to be used as a guidance and counseling media, primarily to enhance elementary school students’ career comprehension. Further, this career pocketbook can be suggested as the media for students’ career guidance and counseling.